2011
DOI: 10.1902/jop.2010.100121
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Acellular Dermal Matrix as a Three‐Dimensional Scaffold for Gingival Fibroblasts Seeding

Abstract: ADM is not suitable as a three-dimensional matrix for gingival fibroblasts ingrowth. Gingival fibroblasts and highly proliferative cells as B16F10 can only be superficially located on ADM, and CGF are negatively affected by culture medium conditioned in ADM, reducing its viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
3
13
0
1
Order By: Relevance
“…On the other hand, significantly higher values of total cell number, cell viability and total protein content were noted for HGF. These results corroborate with those of a recent study (13), in which HGF showed higher cell viability than CGF when seeded on a three-dimensional scaffold.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, significantly higher values of total cell number, cell viability and total protein content were noted for HGF. These results corroborate with those of a recent study (13), in which HGF showed higher cell viability than CGF when seeded on a three-dimensional scaffold.…”
Section: Discussionsupporting
confidence: 92%
“…Some authors have been evaluating non-enzymatic methods of gingival fibroblasts isolation in vitro for the use in gingival augmentation (6,(10)(11)(12)(13)(14). Gingival fibroblast culture in different matrices has been studied and has shown promising results in soft tissues regeneration (12)(13)(14). Fibroblasts are responsible for the normal growth of the organism and are essential in cases where tissue repairs are necessary, being one of the first cells to appear at injured sites.…”
Section: Discussionmentioning
confidence: 99%
“…As fibroblasts have stem‐cell‐like properties and can differentiate to osteoblast‐like cells and have the ability to secret calcified matrix, fibroblasts recently have been utilized as a seeding cell for tissue regeneration for bone and periodontal reconstruction (e.g. ridge augmentation and in tissue‐guided regeneration) . In our present study, our results indicated that HGF cell line produced ALP enzyme with a lower activity after exposure to certain concentrations of caffeine (Figure ).…”
Section: Discussionsupporting
confidence: 59%
“…In addition, fibroblasts are capable of osteoblastic differentiation and possess unique mesenchymal stem‐cell‐like properties with osteogenic and fibrogenic capacity . As gingival fibroblasts share many osteoblast‐like properties, for example, high alkaline phosphatase (ALP) activity, expression of bone associated proteins, and formation of mineralized nodules in in vitro studies, they have been used extensively in the past few years in therapeutic procedures for periodontal tissue regeneration therapy and preprosthetic, pre‐implantology surgeries …”
Section: Introductionmentioning
confidence: 97%
“…Los tejidos del donante se preparan mediante la eliminación de la epidermis y los componentes celulares de la piel reduciendo así la posibilidad de rechazo sobre el injerto. La MDA es entonces crioprotegida y rápi-damente liofilizada, esto para preservar su integridad estructural y bioquímica (13)(14)(15), finalmente aumenta el espesor del tejido y a partir de un punto de vista histológico se adhiere a los tejidos periodontales de forma similar al tejido conectivo y sus cualidades no inmunogénicas hacen que sea viable el trasplante dermal, manteniendo la integridad estructural y la revascularización (3,13).…”
Section: Introductionunclassified